Relationship between 2-Hour Tacrolimus Concentrations and Clinical Outcomes in Long Term Kidney Transplantation - Jeffrey Yin; Tammy Hsu; Janice S Kerr; Robert Steiner; Linda Awdishu (MDPI AG, 2020)
Background: Tacrolimus is routinely monitored using trough concentrations, however, recent data have suggested that area under the curve (AUC) provides better correlation with toxicity and efficacy. Area under the curve is cumbersome to measure, but studies have demonstrated that surrogate time points such as 2-hour concentrations are well correlated with AUC. Methods: This is a single center, retrospective study of adult kidney transplant recipients with 2-hour tacrolimus concentrations measured over three years post-transplant. The primary outcome was to determine the difference in serum creatinine (Scr) in those with 2-hour tacrolimus concentrations greater than 20 ng/mL versus those less than or equal to 20 ng/mL. Results: A total of 150 kidney transplant recipients were included. The mean Scr and glomerular filtration rate were 1.49 ± 1.01 mg/dL and 59 ± 23.2 mL/min/1.73 m2, respectively, for the entire cohort. The rate of donor specific antibody formation was 2% and 8% experienced biopsy-proven rejection. The rate of cytomegalovirus viremia was 2% and BK viremia was 13%. There was no significant difference in kidney function over 36 months for the groups specified a priori. Conclusions: Long-term outcomes of maintaining tacrolimus 2-hour concentrations over 20 ng/mL is favorable with minimal opportunistic infections.